2007
DOI: 10.2355/isijinternational.47.16
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics of Titanium and Oxygen Dissolved in Liquid Iron Equilibrated with Titanium Oxides

Abstract: The equilibrium titanium oxide phase was identified as Ti 3 O 5 (s) for iron melts containing 0.0012-0.25 mass% Ti at 1 873 K. The equilibrium constant of Ti deoxidation reaction for the formation of pure Ti 3 O 5 (s) were estimated as follows. The activity coefficient of Ti in liquid iron at infinite dilution, g°T i(s) was assessed as 0.011, 0.014 and 0.018 at 1 823 K, 1 873 K and 1 923 K, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
61
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(68 citation statements)
references
References 16 publications
6
61
0
1
Order By: Relevance
“…As was shown, 22) these aluminum concentrations do not affect significantly on the experimental results.…”
Section: Resultssupporting
confidence: 55%
See 2 more Smart Citations
“…As was shown, 22) these aluminum concentrations do not affect significantly on the experimental results.…”
Section: Resultssupporting
confidence: 55%
“…It was shown 22) that, for the description of the Fe-Ti-O system, when Ti 3 O 5 and Ti 2 O 3 oxides are the products of deoxidation, it is insufficient to use only the first-order interaction parameters (e Ti O(Fe) ϭϪ0.541; e O Ti(Fe) ϭϪ1.619) 22) and the second-order parameters must be also taken into account (r The oxygen concentrations in melt that are in equilibrium with a given titanium content (reaction (15) …”
Section: Thermodynamic Considerationmentioning
confidence: 99%
See 1 more Smart Citation
“…7(b) that the stability region of calcium titanates (CT) arises while that of liquid calcium aluminates (LCA) significantly decreases, when the titanium content in the molten steel is 50 ppm. Titanium has significant influence on stable phase diagram, and it means that the calcium aluminate stability region becomes Ti O −0.34 38) 0.031 47) 0.026 36) Ca Al -−0.072 51) 0.0007 narrower with titanium content increases. If the titanium content increases to 0.05% or even more, the liquid phase stability areas remains greatly decreasing while solid calcium titanates phases (CT) increase as shown in Fig.…”
Section: Thermodynamic Calculation Of Al-ti-ca-o Complex Inclusionsmentioning
confidence: 99%
“…Furthermore, it is suggested that fine titanium oxides induce high density nucleation sites for the grain refinement technique in oxide metallurgy technology. 1) Due to such importance, a huge number of studies [2][3][4][5][6][7][8][9][10][11][12][13] concerning the Ti and O equilibrium relation have been reported, where the Ti content in liquid iron has been up to 30 mass%. Our previously measured relation 12,13) between the concentration of Ti and O at 1 873 K is reproduced in Fig.…”
Section: Introductionmentioning
confidence: 99%